Respuesta :
take 1/2 of the linear coefient and square it
2/3 times 1/2=1/3
square 1/3 to get 1/9
the constnat is 1/9
it would factor to (x+1/3)^2
2/3 times 1/2=1/3
square 1/3 to get 1/9
the constnat is 1/9
it would factor to (x+1/3)^2
Answer:
[tex]\frac{1}{9}[/tex] is to be added to make [tex]x^2+\frac{2}{3}x[/tex] a perfect square trinomial as [tex](x+\frac{1}{3})^{2}[/tex]
Step-by-step explanation:
Given : [tex]x^2+\frac{2}{3}x[/tex]
We have to find what can be added to [tex]x^2+\frac{2}{3}x[/tex] to form a perfect square trinomial.
Perfect square trinomial is of the form [tex](a+b)^2[/tex]
Consider the given expression [tex]x^2+\frac{2}{3}x[/tex]
Using algebraic identity [tex](a+b)^2=a^2+b^2+2ab[/tex] ,
Comparing , we get, a = x ......(1)
[tex]2ab=\frac{2}{3}x[/tex]
Uisng (1) , we get,
[tex]2b=\frac{2}{3} \\\\ \Rightarrow b=\frac{1}{3}[/tex]
To make it a perfect square trinomial we need to add [tex]b^2[/tex] term
[tex]b^2=\frac{1}{9}[/tex]
Thus, [tex]\frac{1}{9}[/tex] is to be added to make [tex]x^2+\frac{2}{3}x[/tex] a perfect square trinomial as [tex](x+\frac{1}{3})^{2}[/tex]